Oral lichen planus pemphigoid : a case report of a rare disease treated by topical Tacrolimus mouthwash and Hydroxychloroquine - Douley Jeremy; Fricain Jean-Christophe (EDP Sciences, 2023)
Introduction: Oral Lichen Planus Pemphigoid  (LPP) is the rare association of lichen planus and Mucous  Membrane  Pemphigoid  (MMP) whose therapeutic lines are poorly defined. Bilateral and symmetrical reticulated white lesions characteristic of lichen planus (LP) most often precede the painful post-bullous ulcerations of pemphigoid (P). The oral LPP is very rare and the treatment is not codified. This report described a rare case of oral LPP,  successfully treated with an original combo of topical Tacrolimus and hydroxychloroquine. Observation: A 72 yr old patient was referred to the unit of the oral mucosa pathology and oro-facial pain, of the oral surgery service of Bordeaux hospital. He has painful mouth ulcerations accompanied by reticulated and symmetrical white lesions. A biopsy to perform an anatomopathological examination and a direct immunofluorescence founds the anatomopathological characteristics of LP and P.As first line of treatment, local and general corticosteroid therapy was undertaken to reduce inflammation. The result was not totally satisfactory. As second line of treatment topical Tacrolimus and hydroxychloroquine made it possible to reduce drastically the patient's erosive and ulcerated lesions. Conclusion: The combination of topical tacrolimus and HCQ should be considerated as second line of treatment for LPP resistant to corticotherapy.